A Novel Method for Quantifying Intracranial Volume Change by Distraction Osteogenesis for Craniosynostosis. (May 2018) - Brandel, Michael G.; Dalle Ore, Cecilia L.; Reid, Chris M.; Zhang, Wendy W.; Zhu, William; Kpaduwa, Chinwe S.; Lance, Samuel; Meltzer, Hal S.; Gosman, Amanda A.
Abstract : Introduction: Methods of reporting quantitative results for distraction osteogenesis (DO) of craniosynostosis have been inconsistent. Therefore, the efficacy of differing techniques and timing in regard to volume change is not well established, with no uniform metric for comparisons. Given that cranial vault remodeling with DO may be completed with different approaches, analysis was made to determine (1) the relative efficiency of different approaches in expanding intracranial volume (ICV) and (2) the impact of adjusting for ICV growth on measured DO efficiency. Methods: Patients with craniosynostosis were treated with open cranial vault reconstruction combined with internal distraction. Preoperative and postoperative computed tomography scans were used to quantify ICV change. The metric was determined by dividing percent ICV change by total distraction length. The metric was used as a proxy for efficiency to compare posterior and anterior distraction between groups using the Mann-Whitney U test and within a subgroup of patients who underwent 2-stage distraction using the Wilcoxon matched-pairs signed rank test. Results: Twenty patients underwent cranial vault remodeling with DO: 14 unicoronal, 3 bicoronal, 2 multisutural, and 1 lambdoid. Results are reported in medians. Distraction efficiency was 0.99%/mm for primary anterior, unilateral distraction for unicoronal patients (n = 13, aged 9.1 months) and 4.28%/mm for posterior distraction using multiple distractors (n = 4, aged 6.3 months). In terms of the metric, primary posterior distraction was significantly more efficient than primary anterior distraction ( P = 0.007). Three patients who had undergone primary posterior distraction later underwent secondary anterior distraction. Again, posterior distraction was shown to be significantly more efficient (5.16 vs 0.62, P = 0.050). For the unicoronal patients who received anterior unilateral distraction, an adjusted metric was calculated to account for normal intracranial growth. This was found to be 0.39%/mm, which was significantly different from the unadjusted metric ( P = 0.0001). Conclusions: Posterior distraction is more efficient for ICV expansion than anterior distraction, which may have implications for the choice of approach for craniosynostosis repair. In addition, this is the first report of a novel standardized metric for analyzing ICV change achieved by DO. This tool allows for adjusting the efficiency metric for expected ICV growth, which significantly impacts its value.